2019
DOI: 10.1002/tcr.201800191
|View full text |Cite
|
Sign up to set email alerts
|

Beyond OLED: Efficient Quantum Dot Light‐Emitting Diodes for Display and Lighting Application

Abstract: The unique features of solution-processed quantum dots (QDs) including emission tunability in the visible range, high-quality saturated color and outstanding intrinsic stability in environment are highly desired in various application fields. Especially, for the preparation of wide color gamut displays, QDs with high photoluminescence quantum yield are deemed as the optimal fluorescent emitter that has been utilized in the backlight for liquid crystal display. Nevertheless, the commercialization of electricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 147 publications
(114 reference statements)
0
77
0
1
Order By: Relevance
“…Recently, Ji et al also demonstrated that CQD-LEDs with all-inorganic device architectures could possess a high efficiency (20.5 cd A −1 ) and impressive luminance (20,000 cd m −2 ) simultaneously, where nickel oxide (NiO) and zinc oxide (ZnO) were used as HTL and ETL, respectively [ 151 ]. However, relatively few effective inorganic charge transporting materials are available, which restricts the further development of this type of device architecture [ 152 ].…”
Section: Fundamental Concepts Of Impurity-doped Nanocrystal Ledsmentioning
confidence: 99%
“…Recently, Ji et al also demonstrated that CQD-LEDs with all-inorganic device architectures could possess a high efficiency (20.5 cd A −1 ) and impressive luminance (20,000 cd m −2 ) simultaneously, where nickel oxide (NiO) and zinc oxide (ZnO) were used as HTL and ETL, respectively [ 151 ]. However, relatively few effective inorganic charge transporting materials are available, which restricts the further development of this type of device architecture [ 152 ].…”
Section: Fundamental Concepts Of Impurity-doped Nanocrystal Ledsmentioning
confidence: 99%
“…Colloidal quantum dot light-emitting diodes (QLEDs) have drawn much attention due to its unique properties (i.e. tunable color emission spectrum, narrow emission bandwidth and low driving voltage, simple fabrication process) and these advantages make QLED be considered a candidate for next generation display technology [1][2][3][4][5][6][7][8][9][10][11]. For real application, the device performance is important.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…[5][6][7] The technical challenge of QLED devices is that their EQE is limited by the light outcoupling efficiency of the device, which is indeed unresolved because of total internal reection, waveguide (WG) and metal surface absorption (SPP). 8,9 Numerous studies have reported that the light extractions of OLEDs and QLEDs could be enhanced through introduction of internal or external light-extraction layers. [10][11][12][13][14] For example, we have demonstrated that introducing internal PEDOT:PSS grating nanostructures can effectively extract the waveguided light from QLEDs by nanoimprint lithography techniques.…”
Section: Introductionmentioning
confidence: 99%